High-performance MnO2 / MoS2 / SWCNHs ternary composite wave-absorbing material and preparation method thereof
Through the preparation method of MnO2/MoS2/SWCNHs ternary composite material, the existing absorbent materials have been solved, and high-performance electromagnetic wave absorption is achieved, with the characteristics of "thin, light, wide and strong". Suitable for a variety of scenarios.
Patent Information
- Application Number
- CN202411444568.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-07
AI Technical Summary
The existing electromagnetic wave absorbing materials have the disadvantages of high density, poor corrosion resistance, easy oxidation, and narrow absorption frequency band, which are difficult to meet the needs of high-performance absorbing materials.
The preparation method of MnO2/MoS2/SWCNHs ternary composite material is adopted. Through ultrasonic dispersion, solvent-thermal reaction and hydrothermal reaction, the components are evenly distributed and synergistically play a role, and a multi-stage microsphere structure is formed to improve electromagnetic wave absorption performance. .
It realizes high-performance electromagnetic wave absorption, has four major characteristics: "thin, light, wide and strong", which significantly improves the absorption and attenuation effect of electromagnetic waves. It is suitable for a variety of scenarios and replaces traditional high-density and low-performance wave absorption materials.
Smart Images

Figure CN119391369A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a composite wave absorbing material. Background Art
[0002] With the rapid development of 5G and 6G communication technologies, mobile phones, computers and other electronic devices have brought great convenience to people's production and life, but they have also generated serious electromagnetic radiation and pollution, becoming the fourth largest source of pollution after water, atmosphere and noise. It not only affects the normal transmission of electromagnetic signals and interferes with the normal operation of precision electronic instruments and equipment, but also creates the risk of information leakage, and even seriously threatens the ecological environment and human health. For example, severe electromagnetic pollution can cause plant inactivation, gene mutation and even death; long-term exposure to electromagnetic radiation environment can cause dizziness, memory loss, tinnitus, insomnia and other symptoms, and can induce cancer, genetic diseases, fetal malformations, leukemia, etc., and even complete exposure in a short period of time can directly cause death. It can be seen that it is urgent to take effective measures to control the increasingly serious problem of electromagnetic pollution.
[0003] In the above context, the research and development of electromagnetic wave absorbing materials is crucial. Such materials can convert electromagnetic energy into heat or other forms of energy to achieve the purpose of eliminating electromagnetic waves. Metals and their alloys are commonly used traditional absorbing materials, but they have disadvantages such as high density, poor corrosion resistance, easy oxidation, and narrow absorption band. Ideal high-performance absorbing materials should have the four characteristics of "thin, light, wide, and strong", that is, thin matching thickness, light weight, wide absorption band, and strong absorption capacity.
[0004] When existing single-component materials are used as absorbing materials, the electromagnetic parameters are poorly controllable and the loss mechanism is single, exposing a series of shortcomings such as poor impedance matching, weak absorption intensity, and narrow absorption band. These disadvantages make it difficult to meet the needs of actual applications, thus limiting the application of these materials in the field of absorbing waves. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a high-performance MnO2 / MoS2 / SWCNHs ternary composite absorbing material, which is characterized by comprising the following steps:
[0006] S1. Add single-walled carbon nanohorns (SWCNHs) into N,N-dimethylformamide (DMF) solvent and disperse them uniformly by ultrasonication;
[0007] S2. Add (NH4)2MoS4 to the mixed system of S1., continue to perform ultrasonic treatment and heating, and perform solvothermal reaction to obtain MoS2 / SWCNHs hybrid.
[0008] S3. Ultrasonic dispersion of MoS2 / SWCNHs hybrid in water, addition of KMnO4 and stirring until uniform, heating the resulting solution for hydrothermal reaction to obtain a composite material.
[0009] It is worth noting that the present application combines materials of different components to construct a high-performance composite material with a certain structure and morphology, ensuring that the components are evenly distributed and can synergistically exert the functions of the components. It can enrich the heterojunction surface and microstructure of the material, effectively adjust electromagnetic parameters, optimize impedance matching, and enhance microwave absorption and attenuation.
[0010] The present invention starts from the two aspects of composition regulation and microstructure design, and can control the preparation of MnO2 / MoS2 / SWCNHs ternary composite absorbing materials. Through the synergistic effect between the components, the overall absorbing performance of the composite material is effectively improved to meet the requirements of "thin, light, wide and strong" for high-performance absorbing materials. The obtained composite material is suitable for various scenarios such as electronic devices, instruments and meters, military facilities, weapons and equipment, wearable devices, etc., and is expected to replace high-density, low-performance traditional absorbing materials.
[0011] test:
[0012] This application uses the coaxial method to test the wave absorption performance of the MnO2 / MoS2 / SWCNHs ternary composite material. The composite material sample is mixed with paraffin in a certain proportion to make a coaxial ring with an outer diameter of 7.0 mm and an inner diameter of 3.04 mm. The electromagnetic performance test is carried out on a vector network analyzer with a test frequency band of 2 to 18 GHz.
[0013] Furthermore, in step S1., the mass-to-volume ratio of the single-walled carbon nanohorn to N,N-dimethylformamide (DMF) (wherein the unit of mass is g and the unit of volume is L) is 8:(7-8).
[0014] Furthermore, in step S1, the ultrasonic treatment time is 15 minutes to 1.5 hours.
[0015] Furthermore, in steps S1-2, the mass ratio of SWCNHs to (NH4)2MoS4 is 1:(1.5-2.5).
[0016] Furthermore, in step S2, the ultrasonic treatment time is 15 minutes to 1.5 hours. After uniform mixing, the resulting solution is transferred to a hydrothermal kettle and subjected to a solvent thermal reaction at 150 to 220° C. for 4 to 24 hours. After the reaction is completed, the mixture is naturally cooled to room temperature, and the product is filtered, washed, and dried at 40 to 100° C. for 3 to 24 hours to obtain a MoS2 / SWCNHs hybrid.
[0017] Further, in step S3, the mass ratio of MoS2 / SWCNHs hybrid to KMnO4 is 1:0.5-2.5.
[0018] Further, in step S3, after the MoS2 / SWCNHs hybrid is ultrasonically treated for 15 minutes to 1.5, KMnO4 is added and stirred until uniform, and the resulting solution is transferred to a hydrothermal reactor for hydrothermal reaction at 120 to 200°C for 4 to 24 hours. After the reaction product is naturally cooled, it is filtered, washed and vacuum dried at 40 to 100°C for 3 to 24 hours to obtain a composite material.
[0019] The present application claims protection for a high-performance MnO2 / MoS2 / SWCNHs ternary composite absorbing material obtained based on the above method.
[0020] Furthermore, in the composite material, the mass percentage of the MnO2 / MoS2 / SWCNHs ternary composite material is 20 to 50%.
[0021] Furthermore, the material has an absorption frequency band of 2 to 18 GHz.
[0022] Beneficial technical effects of the present invention:
[0023] 1. The preparation method of the MnO2 / MoS2 / SWCNHs ternary composite material of the present invention is a common solvent thermal and hydrothermal method, which does not require complex and harsh processes such as high-temperature calcination. It has the advantages of simple process flow, mild reaction conditions, strong controllability, good repeatability, etc., and is suitable for large-scale industrial production and practical application promotion.
[0024] 2. The MnO2 / MoS2 / SWCNHs ternary composite material of the present invention has a multi-level microsphere structure, which has a large number of pores and voids. While reducing the density of the composite material, it can promote the absorption of electromagnetic waves on the surface of the material, causing multiple emission and scattering of electromagnetic waves inside the material, greatly extending the transmission path of the electromagnetic waves, thereby enhancing the absorption and attenuation of electromagnetic waves. Therefore, the composite material has a significant absorption and attenuation effect on electromagnetic waves.
[0025] 3. The MnO2 / MoS2 / SWCNHs ternary composite absorbing material of the present invention has a wide-band response characteristic, and the effective absorption bandwidth is located in the low, medium and high frequencies, covering the S band (2-4GHz), C band (4-8GHz), X band (8-12GHz) and Ku band (12-18GHz), reflecting the wide-band response characteristics that are difficult for conventional absorbing materials to possess, and is of great value for improving the scope of application of the material and broadening the application scenarios of the material.
[0026] 4. The MnO2 / MoS2 / SWCNHs ternary composite absorbing material of the present invention is a new type of high-efficiency absorbing material with four outstanding characteristics of "thin, light, wide and strong", and has broad application prospects in the field of electromagnetic radiation protection technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the X-ray diffraction (XRD) pattern of the MnO2 / MoS2 / SWCNHs ternary composite material obtained in Example 1.
[0028] Figure 2 This is a scanning electron microscope (SEM) image of the MnO2 / MoS2 / SWCNHs ternary composite material obtained in Example 1.
[0029] Figure 3 This is the transmission electron microscope (TEM) image of the MnO2 / MoS2 / SWCNHs ternary composite material obtained in Example 1.
[0030] Figure 4 This is a high-resolution transmission electron microscopy (HRTEM) image of the MnO2 / MoS2 / SWCNHs ternary composite material obtained in Example 1.
[0031] Figure 5 This is the reflection loss (RL) curve of the MnO2 / MoS2 / SWCNHs ternary composite material obtained in Example 1. DETAILED DESCRIPTION
[0032] The present invention is further described below in conjunction with the embodiments, but it should not be understood that the above subject matter of the present invention is limited to the following embodiments. Without departing from the above technical ideas of the present invention, various substitutions and changes are made according to the common technical knowledge and customary means in the art, which should all be included in the protection scope of the present invention.
[0033] Example 1
[0034] Step 1: 80 mg SWCNHs was added into 80 mL DMF solvent and ultrasonicated for 30 min.
[0035] Step 2: Add 176 mg (NH4)2MoS4, continue ultrasonication for 30 min, transfer the solution to a hydrothermal reactor after mixing evenly, and perform solvothermal reaction at 200 °C for 10 h. After the reaction is completed, cool naturally to room temperature, collect the product by filtration, rinse repeatedly with deionized water and ethanol, and then vacuum dry at 60 °C for 8 h to obtain MoS2 / SWCNHs hybrid.
[0036] Step 3 Take 60 mg of the MoS2 / SWCNHs hybrid obtained in step 1, disperse it in 120 mL of deionized water, ultrasonicate for 30 min until the solution is evenly dispersed, then add 60 mg of KMnO4, stir at room temperature for 30 min, transfer the resulting solution to a hydrothermal kettle, and hydrothermally react at 160 ° C for 6 h. After the reaction is completed, naturally cool to room temperature, collect the product by filtration, rinse repeatedly with deionized water and ethanol, and then vacuum dry at 60 ° C for 8 h to obtain a MnO2 / MoS2 / SWCNHs ternary composite material.
[0037] test:
[0038] The MnO2 / MoS2 / SWCNHs ternary composite material obtained in the above steps was mixed with paraffin in a mass ratio of 4:6, heated at 75°C for 2 to 3 minutes until the paraffin melted, mixed evenly and cooled to room temperature to obtain a block sample, which was transferred to a mold and pressed into a coaxial ring with an outer diameter of 7.0 mm and an inner diameter of 3.04 mm. The electromagnetic properties were tested on a vector network analyzer in the test frequency band of 2 to 18 GHz.
[0039] X-ray diffraction (XRD) was used to characterize the composition and crystal structure of the MnO2 / MoS2 / SWCNHs ternary composite material. The obtained XRD spectrum is shown in Figure 1 As shown. The broad diffraction peaks near 24.8° and 46.1° are characteristic peaks of SWCNHs; the more significant diffraction peaks at 14.1°, 33.5° and 58.9° correspond to the (002), (100) and (110) crystal planes of hexagonal MoS2 crystals respectively; the diffraction peaks at 18.1°, 26.6°, 39.8°, 48.5° and 56.8° correspond to the (200), (310), (211), (411) and (600) crystal planes of α-MnO2 respectively. XRD test results show that the present invention successfully synthesized the MnO2 / MoS2 / SWCNHs ternary composite material.
[0040] Scanning electron microscopy (SEM) was used to characterize the structure and morphology of the MnO2 / MoS2 / SWCNHs ternary composite material. Figure 2 As shown. It can be seen that SWCNHs presents a nano-spherical structure, MnO2 / MoS2 hybrids are sea urchin-like micron-sized spherical structures, and nano- and micron-sized spheres form a multi-level spherical structure. This type of structure has a large number of pores and holes, which is very conducive to multiple reflections and scattering of electromagnetic waves, thereby enhancing the absorption and attenuation of electromagnetic waves. In addition, SWCNHs nanospheres can also be used as dispersants and spacers for MnO2 / MoS2 hybrid microspheres to prevent agglomeration or stacking.
[0041] Transmission electron microscopy (TEM) was used to further observe the microstructure of the MnO2 / MoS2 / SWCNHs ternary composite material. The obtained TEM and HRTEM images are shown in Figure 2. Figure 3 and Figure 4 As shown. It can be seen that the MnO2 nanocrystals wrapped by SWCNHs nanospheres and MoS2 nanosheets are uniformly dispersed in the composite material system, forming a multi-level hybrid structure with rich heterogeneous interfaces. In the HRTEM image, the interplanar spacing of 0.62nm corresponds to the (002) crystal plane of the hexagonal MoS2 crystal, the interplanar spacing of 0.24nm corresponds to the (211) crystal plane of α-MnO2, and the corrugated carbon stripes are the characteristic structure of SWCNHs. SEM and TEM characterization further prove that the present invention successfully synthesized the MnO2 / MoS2 / SWCNHs ternary composite material.
[0042] According to the transmission line theory, the absorption performance parameters of the material are calculated, and the reflection loss (RL) curve is as follows: Figure 5 It can be seen that when the matching thickness is 2mm, at the frequency of 11.5GHz, the corresponding optimal reflection loss value is -60.5dB, and the corresponding effective absorption frequency width is 5.79GHz, which covers part of the X-band and Ku-band, reflecting the dual-band characteristics that are difficult for conventional absorbing materials to have, which is of great value for improving the application scope of materials and broadening the application scenarios of materials.
[0043] Example 2
[0044] Step 1: 80 mg SWCNHs was added into 80 mL DMF solvent and ultrasonicated for 30 min.
[0045] Step 2: Add 176 mg (NH4)2MoS4, continue ultrasonication for 30 min, transfer the solution to a hydrothermal reactor after mixing evenly, and perform solvothermal reaction at 200 °C for 10 h. After the reaction is completed, cool naturally to room temperature, collect the product by filtration, rinse repeatedly with deionized water and ethanol, and then vacuum dry at 60 °C for 8 h to obtain MoS2 / SWCNHs hybrid.
[0046] Step 3 Take 60 mg of the MoS2 / SWCNHs hybrid obtained in step 1, disperse it in 120 mL of deionized water, ultrasonicate for 30 min until the solution is evenly dispersed, then add 60 mg of KMnO4, stir at room temperature for 30 min, transfer the resulting solution to a hydrothermal reactor, and hydrothermally react at 160 ° C for 6 h. After the reaction is completed, cool naturally to room temperature, collect the product by filtration, rinse repeatedly with deionized water and ethanol, and then vacuum dry at 60 ° C for 8 h to obtain a MnO2 / MoS2 / SWCNHs ternary composite material.
[0047] test:
[0048] The MnO2 / MoS2 / SWCNHs ternary composite material obtained in the above steps was mixed with paraffin in a mass ratio of 2:8, heated at 75°C for 2 to 3 minutes until the paraffin melted, mixed evenly and cooled to room temperature to obtain a block sample, which was transferred to a mold and pressed into a coaxial ring with an outer diameter of 7.0 mm and an inner diameter of 3.04 mm. The electromagnetic properties were tested on a vector network analyzer in the test frequency band of 2 to 18 GHz.
[0049] When the matching thickness of the obtained absorbing material is 3mm, the corresponding optimal reflection loss value is -40.5dB at a frequency of 6.8GHz, and the corresponding effective absorption frequency width is 4.32GHz, covering part of the C band and X band.
[0050] Example 3
[0051] Step 1: 80 mg SWCNHs was added into 80 mL DMF solvent and ultrasonicated for 30 min.
[0052] Step 2: Add 176 mg (NH4)2MoS4, continue ultrasonication for 30 min, transfer the solution to a hydrothermal reactor after mixing evenly, and perform solvothermal reaction at 200 °C for 10 h. After the reaction is completed, cool naturally to room temperature, collect the product by filtration, rinse repeatedly with deionized water and ethanol, and then vacuum dry at 60 °C for 8 h to obtain MoS2 / SWCNHs hybrid.
[0053] Step 3 Take 60 mg of the MoS2 / SWCNHs hybrid obtained in step 1, disperse it in 120 mL of deionized water, ultrasonicate for 30 min until the solution is evenly dispersed, then add 60 mg of KMnO4, stir at room temperature for 30 min, transfer the resulting solution to a hydrothermal reactor, and hydrothermally react at 160 ° C for 6 h. After the reaction is completed, cool naturally to room temperature, collect the product by filtration, rinse repeatedly with deionized water and ethanol, and then vacuum dry at 60 ° C for 8 h to obtain a MnO2 / MoS2 / SWCNHs ternary composite material.
[0054] test:
[0055] The MnO2 / MoS2 / SWCNHs ternary composite material obtained in the above steps was mixed with paraffin in a mass ratio of 3:7, heated at 75°C for 2 to 3 minutes until the paraffin melted, mixed evenly and cooled to room temperature to obtain a block sample, which was transferred to a mold and pressed into a coaxial ring with an outer diameter of 7.0 mm and an inner diameter of 3.04 mm. The electromagnetic properties were tested on a vector network analyzer in the test frequency band of 2 to 18 GHz.
[0056] When the matching thickness of the obtained absorbing material is 2.5 mm, the corresponding optimal reflection loss value is -50.8 dB at the frequency of 8.9 GHz, and the corresponding effective absorption frequency width is 5.17 GHz, covering part of the C band and X band.
[0057] Example 4
[0058] Step 1: 80 mg SWCNHs was added into 80 mL DMF solvent and ultrasonicated for 30 min.
[0059] Step 2: Add 176 mg (NH4)2MoS4, continue ultrasonication for 30 min, transfer the solution to a hydrothermal reactor after mixing evenly, and perform solvothermal reaction at 200 °C for 10 h. After the reaction is completed, cool naturally to room temperature, collect the product by filtration, rinse repeatedly with deionized water and ethanol, and then vacuum dry at 60 °C for 8 h to obtain MoS2 / SWCNHs hybrid.
[0060] Step 3 Take 60 mg of the MoS2 / SWCNHs hybrid obtained in step 1, disperse it in 120 mL of deionized water, ultrasonicate for 30 min until the solution is evenly dispersed, then add 60 mg of KMnO4, stir at room temperature for 30 min, transfer the resulting solution to a hydrothermal reactor, and hydrothermally react at 160 ° C for 6 h. After the reaction is completed, cool naturally to room temperature, collect the product by filtration, rinse repeatedly with deionized water and ethanol, and then vacuum dry at 60 ° C for 8 h to obtain a MnO2 / MoS2 / SWCNHs ternary composite material.
[0061] test:
[0062] The MnO2 / MoS2 / SWCNHs ternary composite material obtained in the above steps was mixed with paraffin in a mass ratio of 5:5, heated at 75°C for 2 to 3 minutes until the paraffin melted, mixed evenly and cooled to room temperature to obtain a block sample, which was transferred to a mold and pressed into a coaxial ring with an outer diameter of 7.0 mm and an inner diameter of 3.04 mm. The electromagnetic properties were tested on a vector network analyzer in the test frequency band of 2 to 18 GHz.
[0063] When the matching thickness of the obtained absorbing material is 2 mm, the corresponding optimal reflection loss value is -58.3 dB at a frequency of 12.7 GHz, and the corresponding effective absorption frequency width is 6.03 GHz, covering part of the X and Ku bands.
[0064] Example 5
[0065] Step 1: 80 mg SWCNHs was added into 70 mL DMF solvent and ultrasonicated for 15 min.
[0066] Step 2: Add 120 mg (NH4)2MoS4, continue ultrasonication for 15 min, transfer the solution to a hydrothermal reactor after mixing evenly, and perform solvothermal reaction at 150 °C for 24 h. After the reaction is completed, cool naturally to room temperature, collect the product by filtration, rinse repeatedly with deionized water and ethanol, and then vacuum dry at 40 °C for 24 h to obtain MoS2 / SWCNHs hybrid.
[0067] Step 3 Take 60 mg of the MoS2 / SWCNHs hybrid obtained in step 1, disperse it in 120 mL of deionized water, ultrasonicate it for 15 min until the solution is evenly dispersed, then add 30 mg of KMnO4, stir it at room temperature for 15 min, transfer the resulting solution to a hydrothermal kettle, and hydrothermally react it at 120 ° C for 24 h. After the reaction is completed, it is naturally cooled to room temperature, the product is collected by filtration, repeatedly rinsed with deionized water and ethanol, and then vacuum dried at 40 ° C for 24 h to obtain a MnO2 / MoS2 / SWCNHs ternary composite material.
[0068] test:
[0069] The MnO2 / MoS2 / SWCNHs ternary composite material obtained in the above steps was mixed with paraffin in a mass ratio of 4:6, heated at 75°C for 2 to 3 minutes until the paraffin melted, mixed evenly and cooled to room temperature to obtain a block sample, which was transferred to a mold and pressed into a coaxial ring with an outer diameter of 7.0 mm and an inner diameter of 3.04 mm. The electromagnetic properties were tested on a vector network analyzer in the test frequency band of 2 to 18 GHz.
[0070] When the matching thickness of the obtained absorbing material is 2.5 mm, the corresponding optimal reflection loss value is -53.6 dB at a frequency of 11.1 GHz, and the corresponding effective absorption frequency width is 5.24 GHz, covering part of the X and Ku bands.
[0071] Example 6
[0072] Step 1: 80 mg SWCNHs was added into 70 mL DMF solvent and ultrasonicated for 15 min.
[0073] Step 2: Add 120 mg (NH4)2MoS4, continue ultrasonication for 15 min, transfer the solution to a hydrothermal reactor after mixing evenly, and perform solvothermal reaction at 150 °C for 24 h. After the reaction is completed, cool naturally to room temperature, collect the product by filtration, rinse repeatedly with deionized water and ethanol, and then vacuum dry at 40 °C for 24 h to obtain MoS2 / SWCNHs hybrid.
[0074] Step 3 Take 60 mg of the MoS2 / SWCNHs hybrid obtained in step 1, disperse it in 120 mL of deionized water, ultrasonicate it for 15 min until the solution is evenly dispersed, then add 30 mg of KMnO4, stir it at room temperature for 15 min, transfer the resulting solution to a hydrothermal kettle, and hydrothermally react it at 120 ° C for 24 h. After the reaction is completed, it is naturally cooled to room temperature, the product is collected by filtration, repeatedly rinsed with deionized water and ethanol, and then vacuum dried at 40 ° C for 24 h to obtain a MnO2 / MoS2 / SWCNHs ternary composite material.
[0075] test:
[0076] The MnO2 / MoS2 / SWCNHs ternary composite material obtained in the above steps was mixed with paraffin in a mass ratio of 2:8, heated at 75°C for 2 to 3 minutes until the paraffin melted, mixed evenly and cooled to room temperature to obtain a block sample, which was transferred to a mold and pressed into a coaxial ring with an outer diameter of 7.0 mm and an inner diameter of 3.04 mm. The electromagnetic properties were tested on a vector network analyzer in the test frequency band of 2 to 18 GHz.
[0077] When the matching thickness of the obtained absorbing material is 3mm, the corresponding optimal reflection loss value is -36.7dB at the frequency of 6.1GHz, and the corresponding effective absorption frequency width is 4.25GHz, which almost covers the entire C-band.
[0078] Example 7
[0079] Step 1: 80 mg SWCNHs was added into 70 mL DMF solvent and ultrasonicated for 15 min.
[0080] Step 2: Add 120 mg (NH4)2MoS4, continue ultrasonication for 15 min, transfer the solution to a hydrothermal reactor after mixing evenly, and perform solvothermal reaction at 150 °C for 24 h. After the reaction is completed, cool naturally to room temperature, collect the product by filtration, rinse repeatedly with deionized water and ethanol, and then vacuum dry at 40 °C for 24 h to obtain MoS2 / SWCNHs hybrid.
[0081] Step 3 Take 60 mg of the MoS2 / SWCNHs hybrid obtained in step 1, disperse it in 120 mL of deionized water, ultrasonicate it for 15 min until the solution is evenly dispersed, then add 30 mg of KMnO4, stir it at room temperature for 15 min, transfer the resulting solution to a hydrothermal kettle, and hydrothermally react it at 120 ° C for 24 h. After the reaction is completed, it is naturally cooled to room temperature, the product is collected by filtration, repeatedly rinsed with deionized water and ethanol, and then vacuum dried at 40 ° C for 24 h to obtain a MnO2 / MoS2 / SWCNHs ternary composite material.
[0082] test:
[0083] The MnO2 / MoS2 / SWCNHs ternary composite material obtained in the above steps was mixed with paraffin in a mass ratio of 3:7, heated at 75°C for 2 to 3 minutes until the paraffin melted, mixed evenly and cooled to room temperature to obtain a block sample, which was transferred to a mold and pressed into a coaxial ring with an outer diameter of 7.0 mm and an inner diameter of 3.04 mm. The electromagnetic properties were tested on a vector network analyzer in the test frequency band of 2 to 18 GHz.
[0084] When the matching thickness of the obtained absorbing material is 2 mm, the corresponding optimal reflection loss value is -57.8 dB at a frequency of 9.1 GHz, and the corresponding effective absorption frequency width is 5.79 GHz, covering part of the C band and almost the entire X band.
[0085] Example 8
[0086] Step 1: 80 mg SWCNHs was added into 70 mL DMF solvent and ultrasonicated for 15 min.
[0087] Step 2: Add 120 mg (NH4)2MoS4, continue ultrasonication for 15 min, transfer the solution to a hydrothermal reactor after mixing evenly, and perform solvothermal reaction at 150 °C for 24 h. After the reaction is completed, cool naturally to room temperature, collect the product by filtration, rinse repeatedly with deionized water and ethanol, and then vacuum dry at 40 °C for 24 h to obtain MoS2 / SWCNHs hybrid.
[0088] Step 3 Take 60 mg of the MoS2 / SWCNHs hybrid obtained in step 1, disperse it in 120 mL of deionized water, ultrasonicate it for 15 min until the solution is evenly dispersed, then add 30 mg of KMnO4, stir it at room temperature for 15 min, transfer the resulting solution to a hydrothermal kettle, and hydrothermally react it at 120 ° C for 24 h. After the reaction is completed, it is naturally cooled to room temperature, the product is collected by filtration, repeatedly rinsed with deionized water and ethanol, and then vacuum dried at 40 ° C for 24 h to obtain a MnO2 / MoS2 / SWCNHs ternary composite material.
[0089] test:
[0090] The MnO2 / MoS2 / SWCNHs ternary composite material obtained in the above steps was mixed with paraffin in a mass ratio of 5:5, heated at 75°C for 2 to 3 minutes until the paraffin melted, mixed evenly and cooled to room temperature to obtain a block sample, which was transferred to a mold and pressed into a coaxial ring with an outer diameter of 7.0 mm and an inner diameter of 3.04 mm. The electromagnetic properties were tested on a vector network analyzer in the test frequency band of 2 to 18 GHz.
[0091] When the matching thickness of the obtained absorbing material is 3 mm, the corresponding optimal reflection loss value is -54.4 dB at a frequency of 12.2 GHz, and the corresponding effective absorption frequency width is 5.01 GHz, covering part of the X and Ku bands.
[0092] Example 9
[0093] Step 1: 80 mg SWCNHs was added into 70 mL DMF solvent and ultrasonicated for 15 min.
[0094] Step 2: Add 200 mg (NH4)2MoS4, continue ultrasonication for 1.5 h, transfer the solution to a hydrothermal reactor after mixing evenly, and perform solvothermal reaction at 220 °C for 4 h. After the reaction is completed, cool naturally to room temperature, collect the product by filtration, rinse repeatedly with deionized water and ethanol, and then vacuum dry at 100 °C for 3 h to obtain MoS2 / SWCNHs hybrid.
[0095] Step 3 Take 60 mg of the MoS2 / SWCNHs hybrid obtained in step 1, disperse it in 130 mL of deionized water, ultrasonicate for 15 min until the solution is evenly dispersed, then add 150 mg of KMnO4, stir at room temperature for 15 min, transfer the resulting solution to a hydrothermal kettle, and hydrothermally react at 200 ° C for 4 h. After the reaction is completed, cool naturally to room temperature, collect the product by filtration, rinse repeatedly with deionized water and ethanol, and then vacuum dry at 100 ° C for 3 h to obtain a MnO2 / MoS2 / SWCNHs ternary composite material.
[0096] test:
[0097] The MnO2 / MoS2 / SWCNHs ternary composite material obtained in the above steps was mixed with paraffin in a mass ratio of 4:6, heated at 75°C for 2 to 3 minutes until the paraffin melted, mixed evenly and cooled to room temperature to obtain a block sample, which was transferred to a mold and pressed into a coaxial ring with an outer diameter of 7.0 mm and an inner diameter of 3.04 mm. The electromagnetic properties were tested on a vector network analyzer in the test frequency band of 2 to 18 GHz.
[0098] When the matching thickness of the obtained absorbing material is 2 mm, the corresponding optimal reflection loss value is -55.5 dB at a frequency of 11.3 GHz, and the corresponding effective absorption frequency width is 4.89 GHz, covering part of the X and Ku bands.
[0099] Example 10
[0100] Step 1: 80 mg SWCNHs was added into 70 mL DMF solvent and ultrasonicated for 15 min.
[0101] Step 2: Add 200 mg (NH4)2MoS4, continue ultrasonication for 1.5 h, transfer the solution to a hydrothermal reactor after mixing evenly, and perform solvothermal reaction at 220 °C for 4 h. After the reaction is completed, cool naturally to room temperature, collect the product by filtration, rinse repeatedly with deionized water and ethanol, and then vacuum dry at 100 °C for 3 h to obtain MoS2 / SWCNHs hybrid.
[0102] Step 3 Take 60 mg of the MoS2 / SWCNHs hybrid obtained in step 1, disperse it in 130 mL of deionized water, ultrasonicate for 15 min until the solution is evenly dispersed, then add 150 mg of KMnO4, stir at room temperature for 15 min, transfer the resulting solution to a hydrothermal kettle, and hydrothermally react at 200 ° C for 4 h. After the reaction is completed, cool naturally to room temperature, collect the product by filtration, rinse repeatedly with deionized water and ethanol, and then vacuum dry at 100 ° C for 3 h to obtain a MnO2 / MoS2 / SWCNHs ternary composite material.
[0103] test:
[0104] The MnO2 / MoS2 / SWCNHs ternary composite material obtained in the above steps was mixed with paraffin in a mass ratio of 2:8, heated at 75°C for 2 to 3 minutes until the paraffin melted, mixed evenly and cooled to room temperature to obtain a block sample, which was transferred to a mold and pressed into a coaxial ring with an outer diameter of 7.0 mm and an inner diameter of 3.04 mm. The electromagnetic properties were tested on a vector network analyzer in the test frequency band of 2 to 18 GHz.
[0105] When the matching thickness of the obtained absorbing material is 2.5 mm, the corresponding optimal reflection loss value is -31.7 dB at a frequency of 5.2 GHz, and the corresponding effective absorption frequency width is 4.44 GHz, covering part of the S band and almost the entire C band.
[0106] Embodiment 11
[0107] Step 1: 80 mg SWCNHs was added into 70 mL DMF solvent and ultrasonicated for 15 min.
[0108] Step 2: Add 200 mg (NH4)2MoS4, continue ultrasonication for 1.5 h, transfer the solution to a hydrothermal reactor after mixing evenly, and perform solvothermal reaction at 220 °C for 4 h. After the reaction is completed, cool naturally to room temperature, collect the product by filtration, rinse repeatedly with deionized water and ethanol, and then vacuum dry at 100 °C for 3 h to obtain MoS2 / SWCNHs hybrid.
[0109] Step 3 Take 60 mg of the MoS2 / SWCNHs hybrid obtained in step 1, disperse it in 130 mL of deionized water, ultrasonicate for 15 min until the solution is evenly dispersed, then add 150 mg of KMnO4, stir at room temperature for 15 min, transfer the resulting solution to a hydrothermal kettle, and hydrothermally react at 200 ° C for 4 h. After the reaction is completed, cool naturally to room temperature, collect the product by filtration, rinse repeatedly with deionized water and ethanol, and then vacuum dry at 100 ° C for 3 h to obtain a MnO2 / MoS2 / SWCNHs ternary composite material.
[0110] test:
[0111] The MnO2 / MoS2 / SWCNHs ternary composite material obtained in the above steps was mixed with paraffin in a mass ratio of 3:7, heated at 75°C for 2 to 3 minutes until the paraffin melted, mixed evenly and cooled to room temperature to obtain a block sample, which was transferred to a mold and pressed into a coaxial ring with an outer diameter of 7.0 mm and an inner diameter of 3.04 mm. The electromagnetic properties were tested on a vector network analyzer in the test frequency band of 2 to 18 GHz.
[0112] When the matching thickness of the obtained absorbing material is 3mm, the corresponding optimal reflection loss value is -59.7dB at the frequency of 8.8GHz, and the corresponding effective absorption frequency width is 6.43GHz, covering part of the C band and the entire X band.
[0113] Example 12
[0114] Step 1: 80 mg of SWCNHs was added into 70 mL of N,N-dimethylformamide (DMF) solvent and ultrasonicated for 15 min.
[0115] Step 2: Add 200 mg (NH4)2MoS4, continue ultrasonication for 1.5 h, transfer the solution to a hydrothermal reactor after mixing evenly, and perform solvothermal reaction at 220 °C for 4 h. After the reaction is completed, cool naturally to room temperature, collect the product by filtration, rinse repeatedly with deionized water and ethanol, and then vacuum dry at 100 °C for 3 h to obtain MoS2 / SWCNHs hybrid.
[0116] Step 3 Take 60 mg of the MoS2 / SWCNHs hybrid obtained in step 1, disperse it in 130 mL of deionized water, ultrasonicate for 15 min until the solution is evenly dispersed, then add 150 mg of KMnO4, stir at room temperature for 15 min, transfer the resulting solution to a hydrothermal kettle, and hydrothermally react at 200 ° C for 4 h. After the reaction is completed, cool naturally to room temperature, collect the product by filtration, rinse repeatedly with deionized water and ethanol, and then vacuum dry at 100 ° C for 3 h to obtain a MnO2 / MoS2 / SWCNHs ternary composite material.
[0117] test:
[0118] The MnO2 / MoS2 / SWCNHs ternary composite material obtained in the above steps was mixed with paraffin in a mass ratio of 5:5, heated at 75°C for 2 to 3 minutes until the paraffin melted, mixed evenly and cooled to room temperature to obtain a block sample, which was transferred to a mold and pressed into a coaxial ring with an outer diameter of 7.0 mm and an inner diameter of 3.04 mm. The electromagnetic properties were tested on a vector network analyzer in the test frequency band of 2 to 18 GHz.
[0119] When the matching thickness of the obtained absorbing material is 3.5 mm, the corresponding optimal reflection loss value is -52.2 dB at a frequency of 12.7 GHz, and the corresponding effective absorption frequency width is 5.49 GHz, covering part of the X and Ku bands.
[0120] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. The present invention can also have other forms of embodiments according to the above structures and functions, which are not listed one by one. Therefore, any technician familiar with the technical field within the technical scope disclosed by the present invention, according to the technical solution and inventive concept of the present invention, shall be covered within the protection scope of the present invention.
Claims
1. A method for preparing a high-performance MnO2 / MoS2 / SWCNHs ternary composite absorbing material, characterized in that: The following steps are involved: S1. adding the single-walled carbon nanohorns (SWCNHs) into N,N-dimethylformamide (DMF) solvent and uniformly dispersing by ultrasonication; S2. Add (NH4)2MoS4 to the mixed system of S1., continue to perform ultrasonic treatment and heating, and perform solvothermal reaction to obtain MoS2 / SWCNHs hybrid. S3. Ultrasonic dispersion of MoS2 / SWCNHs hybrid in water, addition of KMnO4 and stirring until uniform, heating the resulting solution for hydrothermal reaction to obtain a composite material.
2. A high-performance MnO2 / MoS2 / SWCNHs ternary composite absorbing material and a preparation method thereof according to claim 1, characterized in that: In step S1., the mass volume ratio (g / L) of the single-walled carbon nanohorn to N,N-dimethylformamide (DMF) is 8:(7-8).
3. The high-performance MnO2 / MoS2 / SWCNHs ternary composite absorbing material and preparation method thereof according to claim 1, characterized in that: In step S1, the ultrasonic treatment time is 15 minutes to 1.5 hours.
4. The high-performance MnO2 / MoS2 / SWCNHs ternary composite absorbing material and preparation method thereof according to claim 1, characterized in that: In steps S1-2, the mass ratio of SWCNHs to (NH4)2MoS4 is 1:(1.5-2.5).
5. The high-performance MnO2 / MoS2 / SWCNHs ternary composite absorbing material and preparation method thereof according to claim 1, characterized in that: In step S2, the ultrasonic treatment time is 15 minutes to 1.5 hours, and the resulting solution is transferred to a hydrothermal autoclave after being evenly mixed; after the reaction is completed, it is naturally cooled to room temperature, and the product is filtered, washed, and dried at 40 to 100° C. for 3 to 24 hours to obtain a MoS2 / SWCNHs hybrid.
6. The high-performance MnO2 / MoS2 / SWCNHs ternary composite absorbing material and preparation method thereof according to claim 1, characterized in that: In step S3, the mass ratio of MoS2 / SWCNHs hybrid to KMnO4 is 1:0.5-2.
5.
7. The high-performance MnO2 / MoS2 / SWCNHs ternary composite absorbing material and preparation method thereof according to claim 1, characterized in that: In step S3, after the MoS2 / SWCNHs hybrid is ultrasonically treated for 15 minutes to 1.5 minutes, KMnO4 is added and stirred until uniform, and the resulting solution is transferred to a hydrothermal autoclave; after the reaction product is naturally cooled, it is filtered, washed and vacuum dried at 40 to 100°C for 3 to 24 hours to obtain a composite material. A high performance MnO2 / MoS2 / SWCNHs-1- Ternary composite absorbing material and preparation method thereof.
8. A high-performance MnO2 / MoS2 / SWCNHs ternary composite absorbing material obtained by the method described in any one of claims 1 to 7.
9. The high performance MnO2 / MoS2 / SWCNHs ternary composite absorbing material according to claim 8, characterized in that: In the composite material, the mass percentage of the MnO2 / MoS2 / SWCNHs ternary composite material is 20-50%.
10. A high performance MnO2 / MoS2 / SWCNHs ternary composite absorbing material according to claim 8 or 9, characterized in that: The material's wave absorption frequency band is 2 to 18 GHz.